Identity and Creativity: Putting Two and Two Together (LEARNing Landscapes, 2012)
"Questions, not method, are the heart of research" (Hendry, 2010, p. 73). Prompted by untutored intuition in the form of questions generated from two stories about teaching and educational leadership, this investigation looks for insights, not answers, to the mystery of identity and creativity. Putting two and two together reveals an intangible "in-between" (Arendt, 1974); distinguishes thinking and knowing (Arendt, 1971); elucidates intuition and intellect (Bergson, 1998/1907); exposes emotion and feelings as vital aspects of reason (Damasio, 1994; 1999); and conspires to revitalize the meaning and purpose of education.
Keywords: Question; research; teaching; educational leadership; identity; creativity; emotion; feeling; education